English Camp as Learning and Teaching Atmosphere of Speaking Ability Development - Ready, A. Fawazien; Indrayani, Ninuk (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
Teaching and learning English method recently have become very important issue to discuss as it is seen to not be effective anymore. This is proven by the majority of students who cannot achieve the learning target even when they learn English for many years. English Camp serves as a method that gives the teacher and the student a new learning atmosphere in which it can be done either inside or outside the classroom. This study employed a descriptive qualitative approach where the data were collected through observation, interview, and documentation. The date then was analyzed by using triangulation consisting the process of; data condensation, the display of the data, conclusion verification. The result of this research suggested that English Camp is perceived as an effective atmosphere for English learners and teachers in achieving the learning objective. It can improve students speaking performance for speaking is all about forming habits when this is the focus of the entire learning activities.